ANALISIS BUTIR TRY OUT UJIAN NASIONAL MATEMATIKA SEKOLAH DASAR DI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2017 - Martalia Ardiyaningrum; Cahya Kusuma; Trisniawati Trisniawati (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2018)
This study aims at studying the national examination conducted by â€œPhytagorasâ€ Mathematics Course. This research is a descriptive study conducted to test the national examination of elementary school, specifically in its mathematics subject. The data used in this research is the results of Indonesian national exam simulation test conducted by â€œPhytagorasâ€ mathematics course in 2017. The data of this study are obtained from 919 sixth-grade students who had accomplished mathematical tutoring in â€œPhytagorasâ€ mathematics course. The results of the data analysis showed that there are 5 out of 40 mathematical test items that need to be evaluated due to its level of difficulty. Those five items are suggested to be reformatted and revised for the improvements of the next national exam simulation test.